Antifungal potential of essential oil from Zanthoxylum pseudodumosum Beurton, an endemic species of Cuba - Martín Cruz, Lisbet; Guerra de León, José Orestes; Ojito Ramos, Katia; Stevanovic, Tatjana; Kasangana, Pierre Betu; Portal Villafaña, Orelvis (My University, 2020)
For the first time, the essential oil from leaves of Zanthoxylym pseudodumosum, an endemic species from central Cuba, was analysed by gas chromatography - flame ionization detector (GC-FID) and gas chromatography – mass spectrometry (GC–MS). A total of seventeen compounds representing 85.7% of the oil were identified and the major components were revealed to be mainly sesquiterpenes hydrocarbons, among which the major were β-caryophyllene, (32.01%), germacrene D (14.89%) and α-selinene (8.67%). Antifungal activity and the capacity of the essential oil to induce oxidative stress were evaluated against the phytopathogenic fungus Alternaria solani. The results showed that the oil exhibited an inhibitory effect on mycelial growth of A. solani and caused oxidative stress by increasing the concentration of malondialdehyde (MDA) in comparison with the control. These findings therefore confirm the antifungal effect of Z. pseudodumosum leaf essential oil and the potential uses of its use as a natural product, an alternative to chemical fungicides.
Keywords: Zanthoxylum pseudodumosum; Essential Oil; Chemical Composition; Antifungal Activity; Antioxidant Activity